L'injure mise en scène. A propos d'un « insulteur public » dans la société baghdadienne du XIe siècle - Evelyne Larguèche (Revue des Mondes Musulmans et de la Méditerranée)
The evocation of a figure defined as a public « insultor » in the 11e c. Baghdadi society, as it appears in the book of Abou-Moutahhar al-Azdî, translated from Arabic with the title 24 hours in the life of a "rabble", needed definitely a closer inspection. As he follows the unfolding of this 24 hours, the reader understands that it is an entertainment, which follows well defined rules, and wherein actors and spectators play established roles. The paper analyses and comments the ways and techniques used for this staging of insult.